AB0315 The potential association between rheumatoid arthritis and traditional cardiovascular risk factors: a meta-analysis of controlled studies. (15th June 2017) - Filhol, E; Gaujoux-Viala, C; Combe, B; Morel, J; Hua, C; Nutz, A; Lukas, C; Flaisler, F
Abstract : Background: Systemic inflammation is the cornerstone of both rheumatoid arthritis (RA) and atherosclerosis. RA is currently considered as a cardiovascular risk factor. Objectives: The aim of this systematic review was to assess the association between RA and the traditional cardiovascular risk factors (hypertension, dyslipidemia, diabete mellitus, and atherosclerosis) in RA patients in comparison to the general population. Methods: We systematically searched literature (via Pubmed, Cochrane and abstracts from recent ACR and EULAR congresses) up to March 2016 for observational studies providing data concerning the presence of a traditional cardiovascular risk factor (among hypertension, dyslipidemia, diabetes mellitus, atherosclerosis) in patients with RA and in a control group. A meta-analysis of the relative risk (RR) concerning patients with RA in relation to the control group was performed for each cardiovascular risk factor. Results: Out of 5714 screened references, 13 studies were included. Due to lack of data, atherosclerosis studies could not be included in this meta-analysis. For hypertension and diabetes, an increased risk was observed: RR =1.15 [95% CI 1.07–1.24], p=0.0003 and RR=1.11 [1.04–1.19], p=0.001, respectively. On the contrary, not any association was found with the dyslipidemia (RR=0.93 [0.77–1.12], p=0.43). Conclusions: This meta-analysis highlights a moderate excess risk of hypertension and diabetes among patients with RA relative to the general population. A comprehensive identification of cardiovascular risk profile of RA is an opportunity to improve health management of these patients. Future research is crucial in order to establish to what extent the control of modifiable risk factors can improve cardiovascular outcome of these patients. Disclosure of Interest: None declared